Konten BXB Melalui Media Tiktok pada Kpopers dalam Normalisasi LGBT: Studi Kasus Fandom NCTZEN - Palan Taran, Arsyifa; Asep Gunawan; Putri Ria Angelina (Universitas Ibn Khaldun Bogor, 2025)
K-pop culture cannot be underestimated because it has managed to attract the attention of many K- Popers through music videos and boy groups made in South Korea. But unfortunately, there are not a few adult scenes contained in K-Pop culture that are shown continuously so that it becomes commonplace among K-Popers, especially from the NCTZEN fandom or NCT boy group fans. One of them is boy love boy (BxB) homosexual content on TikTok media which features romantic relationships between male idols and other male idols. BxB homosexual content gets a lot of support from fans. This is considered worrying, considering that homosexual content itself is a part of lesbian, gay, biseksual, transgender (LGBT) and the current rampant efforts to normalize LGBT. Therefore this study aims: 1. To find out how boy loves boy homosexual content forms on TikTok, 2. To know why K-Popers like boy love boy homosexual content, 3. To know how homosexual content can be a trigger for normalization. This study uses a qualitative method with a case study approach. The results of the study show that: 1. The form of boy love boy homosexual content on TikTok is like the excited moments of NCT members, concert fan-cams, edited videos with additional romantic back sounds and captions, member interactions such as stares and hugs, 2. Reasons for K- Popers like boy love boy homosexual content because of bias, feeling excited, and an alternative to healing mental illness, 3.Boy love boy homosexual content triggers the normalization of LGBT because it is watched continuously.